2005
DOI: 10.1093/humrep/dei071
|View full text |Cite
|
Sign up to set email alerts
|

Is granulocyte colony-stimulating factor level predictive for human IVF outcome?

Abstract: G-CSF is involved in follicle development and may be a predictor of IVF outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 34 publications
2
56
0
2
Order By: Relevance
“…The majority of the cytokines reached their peak levels at the time of OPU, coinciding with the maximal levels of FSH and HCG. In support of our findings, previous studies have found a gradual increase of serum macrophage colony-stimulating factor (M-CSF) and granulocyte colonystimulating factor (G-CSF) throughout ovarian stimulation in IVF cycles (Nishimura et al, 1998;Salmassi et al, 2005;Salmassi et al, 2010). IFN-γ, IL-4 and TNF have been studied after lymphocyte activation with PMA/ionomycin before and after ovarian stimulation (Kalu et al, 2008), and IL-10 has been analyzed in serum during IVF treatment (Wu et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…The majority of the cytokines reached their peak levels at the time of OPU, coinciding with the maximal levels of FSH and HCG. In support of our findings, previous studies have found a gradual increase of serum macrophage colony-stimulating factor (M-CSF) and granulocyte colonystimulating factor (G-CSF) throughout ovarian stimulation in IVF cycles (Nishimura et al, 1998;Salmassi et al, 2005;Salmassi et al, 2010). IFN-γ, IL-4 and TNF have been studied after lymphocyte activation with PMA/ionomycin before and after ovarian stimulation (Kalu et al, 2008), and IL-10 has been analyzed in serum during IVF treatment (Wu et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Salmassi et al evaluated 93 women who underwent IVF; in their study, patients who became pregnant revealed a continuous increase in serum GCSF level from the day of embryo transfer to the day of implantation and from the day of confirmation of pregnancy to gestation; in contrast, those patients who did not become pregnant initially showed a slight increase in GCSF level, then with the failure of implantation as the GCSF level decreased significantly (Salmassi et al 2005). The authors concluded that this cytokine could have an important function in achieving or maintaining pregnancy (Salmassi et al 2005).…”
Section: The Role Of Gcsf In Implantation and Pregnancymentioning
confidence: 99%
“…Salmassi et al evaluated 93 women who underwent IVF; in their study, patients who became pregnant revealed a continuous increase in serum GCSF level from the day of embryo transfer to the day of implantation and from the day of confirmation of pregnancy to gestation; in contrast, those patients who did not become pregnant initially showed a slight increase in GCSF level, then with the failure of implantation as the GCSF level decreased significantly (Salmassi et al 2005). The authors concluded that this cytokine could have an important function in achieving or maintaining pregnancy (Salmassi et al 2005). In another study, Rahmati and coworkers demonstrated significantly lower levels of GCSF receptors at the maternal-fetal interface in infertile women with implantation failure, and interestingly, stimulation with high-dose GCSF was able to increase the expression of GCSF receptors in these patients (Rahmati et al 2014).…”
Section: The Role Of Gcsf In Implantation and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…G-CSF is also secreted by cells of the reproductive tract: human luteinized follicular granulosa cells (12), endometrial cells (13), and cells from decidual, placental (14) and various foetal tissues (15). At ovulation, G-CSF concentrations are much higher in FF than in serum (6). Studies using western blot and immunohistochemistry techniques have located the G-CSF protein and its receptor in the ovary, mainly in the granulosa cells of the follicle and in luteal cells (12).…”
Section: Introductionmentioning
confidence: 99%